Examining Students' Critical Thinking Skills in Addressing Contextual Matrix Problems Within the Tourism Travel Planning Context - Siswanto, Deny Hadi; Andriyani, Andriyani (Al-Khawarizmi, 2024)
The primary aim of this study is to provide an in-depth exploration of the critical thinking abilities exhibited by students when they are confronted with problem-solving tasks involving contextual matrices within the domain of Tourism Travel Planning and Management. To achieve this objective, the qualitative descriptive method is employed, involving a cohort of 30 students from the XI grade of Dirgantara Putra Bangsa Vocational High School as the research participants. The research methodology encompasses the utilization of research tools, including critical thinking skills assessment sheets and interview guidelines. The analysis of the gathered data reveals significant insights: 1) the focus indicator highlights a critical thinking ability percentage of 43.33%; 2) the reason indicator showcases a percentage of 35.00%; 3) the inference indicator indicates a percentage of 46.66%; 4) the situation indicator demonstrates a percentage of 61.11%; 5) the clarity indicator registers a percentage of 40.83%; and 6) the overview indicator presents a percentage of 31.66%. In summary, the average percentage of students' critical thinking skills is calculated to be 43.09%, placing it within the low-level category.